Effectiveness of using Canva Application to Improve Learning Outcomes of Tenth Grades Students - Friska, Junita; Pramuaniati, Isda; Mahriyuni (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
The influence of the use of supportive learning media in today's modern times is linked to low student achievement on French language learning, especially on French language learning material. The purpose of this research was to determine the effectiveness of using the Canva application on improving the French language learning outcomes of students at tenth grade. This research is quasi-experimental research. This study is used sampling technique which is simple random. The selection of sample members from the population is done randomly without considering the existing strata in the population. This research used two classes, namely X IPA class 1 as an experimental class (Implementation of Canva app) and X IPA class 4 as a control class using only Whatsapp. The data collection technique in this research was in the form of a test consisting of a pre-test and a post-test. Based on the t-test calculations that were performed in the experimental class and the control class, the sig. 000 then if the probability value is sig (two-sided) or (sig 0.05) then Ho is accepted. So, there is the effectiveness of using Canva app to increase the French language learning outcomes of tenth grade students.